Особливості соціального захисту осіб, які втратили годувальника - Ярошик, Дарина Анатоліївна; Yaroshyk, Daryna Anatoliivna (Національний університет "Львівська політехніка", 2024)
В умовах складної соціально-економічної ситуації в Україні, погіршеної військовими діями, економічною нестабільністю та пандемією COVID-19, проблема соціального захисту осіб, які втратили годувальника, набуває особливої гостроти та актуальності. Це зумовлює актуальність дослідження проблем і перспектив функціонування системи соціального захисту осіб, які втратили годувальника в складній соціально-економічній ситуації в Україні. Об’єкт дослідження: система соціального захисту населення в Україні. Предмет дослідження: особливості функціонування та напрямки вдосконалення системи соціального захисту осіб, які втратили годувальника. Мета дослідження – дослідити особливості функціонування та сформувати напрямки вдосконалення системи соціального захисту осіб, які втратили годувальника. Результати дослідження: у роботі розглянуто практичні пропозиції щодо покращення ефективності системи соціального захисту через цифровізацію послуг, підвищення адресності допомоги та адаптацію законодавства до європейських стандартів.

In the context of the difficult socio-economic situation in Ukraine, aggravated by military operations, economic instability and the COVID-19 pandemic, the problem of social protection of persons who have lost their breadwinners is becoming particularly acute and relevant. This makes it relevant to study the problems and prospects of the functioning of the social protection system for persons who have lost their breadwinners in the difficult socio-economic situation in Ukraine. Object of research: social protection system in Ukraine. Subject of research: features of the functioning and directions for improving the system of social protection for people who have lost their breadwinner. The purpose of the study is to investigate the features of the functioning and formulate directions for improving the social protection system for people who have lost their breadwinner. Research results: the paper considers practical proposals for improving the efficiency of the social protection system through the digitalization of services, increasing the targeting of assistance, and adapting legislation to European standards.
Peculiarities of social protection of persons who have lost their breadwinner
Keywords: 6.232.00.00; соціальний захист; втрата годувальника; пенсійне забезпечення; соціальні виплати; децентралізація; адресна допомога; social protection; loss of breadwinner; pension provision; social payments; decentralization; targeted assistance. List of sources used: Barannyk L. B. Financial support of the social protection system: theoretical aspect. DSFA Bulletin. Economic Sciences. 2014. No. 1. pp. 8–15. Decentralization Roadmap: Reform of Local Self-Government and Territorial Organization of Power. URL: https://decentralization.gov.ua/news/17406